Association and Sequence Rules of Events in an lnvestment Analysis of Agrotourism Farms - Lasek, Mirosława; Nowak, Ewa; Pęczkowski, Marek (Turyzm/Tourism, 2008)
The article presents an attempt to predict the course of development activity on agrotourism farms. A well-known marketing technique, market basket analysis, has been implemented which concerns the interdependencies of investments undertaken by individual agrotourism farms. Due to the discovery of interdependencies between different features, rules can be created: if feature A accompanies a particular event it may be expected that feature B will accompany this event as well. In this case, investments made Jointly by agrotourism farms will be considered in the order in which they are made. Association analysis and sequence analysis were conducted with the SAS Enterprise Miner programme (2003). Association analysis will help find out what investments have been implemented at individual farms simultaneously, while sequence analysis will allow identification of investments consecutively implemented by farms measured at specific intervals. The analysis has been conducted using the example of the Świętokrzyskie Województwo.